2009
DOI: 10.1149/1.3224113
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Pt Growth on Polycrystalline Au: Surface-Limited Redox Replacement of Overpotentially Deposited Ni Monolayers

Abstract: The catalyst system Pt/Au has been the subject of many studies recently, ranging from formic acid oxidation to oxidative studies for direct alcohol fuel cells. This paper outlines the use of overpotential Ni deposition as an intermediary for the creation of model overlayer/substrate Pt/Au catalysts with atomic monolayer (ML)-level thickness control. Deposition of Pt on polycrystalline Au was conducted via Ni surface-limited redox replacement. By electrodepositing a controlled layer of Ni on Au and exposing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…This agrees with previous studies which predicted that the first monolayer of Pt on Au would exhibit greater d-band distortion compared to the following monolayers [5]. Figure 4 illustrates an effect that we have previously reported [26] but now explore in more detail; the shift of the reduction feature to more negative voltages for ultrathin Pt deposits. It has been shown that the reduction peak after oxidation to 1.5 V corresponds to OH -desorption from the surface [27][28][29].…”
Section: Evidence For Electron Transfer In Pt Filmsupporting
confidence: 90%
“…This agrees with previous studies which predicted that the first monolayer of Pt on Au would exhibit greater d-band distortion compared to the following monolayers [5]. Figure 4 illustrates an effect that we have previously reported [26] but now explore in more detail; the shift of the reduction feature to more negative voltages for ultrathin Pt deposits. It has been shown that the reduction peak after oxidation to 1.5 V corresponds to OH -desorption from the surface [27][28][29].…”
Section: Evidence For Electron Transfer In Pt Filmsupporting
confidence: 90%
“…Cu-mediated growth is preferable to the direct galvanic growth of Pt, which would result in larger Pt nuclei. This type of redox replacement has been performed in the past for noble metals replacing Cu, 16,17 Ni, 18,19 and other metals on various substrates. Figure 1 shows FESEM top-view images of the fabricated electrodes.…”
Section: ' Resultsmentioning
confidence: 99%
“…Among several strategies to synthesize Ni oxide, electrochemical deposition technique is a simple method with several advantages [25,26]. In this work, we describe an approach to deposit Ni oxide nanoparticles on TiO 2 nanotubes by an optimized electrochemical technique and then explore the photocatalysis of Ni oxide loaded TiO 2 nanotubes under UV and visible light conditions.…”
Section: +mentioning
confidence: 99%